Biodiesel production from a free fatty acid containing Karanja oil by a single-step heterogeneously catalyzed process. Issue 5 (8th April 2016) - Gupta, Arun Kumar; Kiro, Mani Rahul; Deo, Goutam
ABSTRACT: Karanja oil, containing 6.2% free fatty acids (FFAs), was considered for biodiesel production using a single-step solid-phase acid catalyzed process. Different types of zeolites and Amberlyst15 catalysts were tested and biodiesel was produced. Under similar conditions, the highest biodiesel yield was achieved using an Amberlyst15 catalyst, which contained 3–5% of moisture. The effects of operating parameters of the reaction such as reaction temperature, catalyst amount, and methanol-to-oil ratio were studied. An increase of methanol:oil ratio revealed a non-monotonic increase in biodiesel yields. Similar non-monotonic behavior was observed when Jatropha oil was used. Leaching and catalyst reusability were also considered. No significant effects of leaching were observed and catalyst reusability appeared to be affected by methanol interactions. The presence of a co-solvent, Tetrahydrofuran (THF), increased the biodiesel yield. Furthermore, an optimum amount of THF (THF:methanol volume ratio of 1:2) gave rise to the highest biodiesel yield. A biodiesel yield of 93% was achieved at 120 °C using a single-step process with Amberlyst15 as a catalyst, THF as a co-solvent, and a methanol:oil ratio of 30:1.